0229 Snap40: A Wearable Stress Monitor And Performance Regulator. (1st November 2014) - McCann, Christpher
Abstract : Context: It is clear that stress induces significant physiological and psychological changes that have an adverse affect on an individuals health, as well as on their work performance. 1 In the context of healthcare, this can have a negative impact on practice, 2 whilst research has shown that stress interventions have a positive impact on trainee performance. 3 Description of innovation: snap40 has developed a novel wristband that uses multiple sensors to monitor an individuals physiological and emotional state across a range of indicators. These indicators predict stress levels, allowing self-monitoring and targeted interventions to take place. The snap40 wristband is taking part in a trial of stress management training among medical students in simulation at the University of Dundee beginning in October 2014. snap40 also plans to use their product to improve patient safety, pre-emptively monitoring the health of patients alerting healthcare staff via mobile devices as a deterioration begins to occur, allowing interventions to be put in place earlier. Anticipated Improvements snap40's aim is to provide healthcare trainees and professionals with a continuous means of self-monitoring their stress, allowing them to regulate their performance. In addition, the wristband provides an easy way for trainers to monitor the stress levels of their trainees. For example, surgical trainees in simulation could be subjected to stress and their response monitored for future debriefing sessions. From a patient safety perspective, snap40 aims to save lives, as well as reduce patient length of stay thus reducing expenditure and resource stress. Take home messages: snap40 has developed a wristband that monitors an individual's physiological and emotional state. The wristband, when used in training, allows healthcare trainees to self-monitor their stress levels, allowing regulation of performance. The wristband, when used in care, increases patient safety by alerting healthcare staff earlier to patient deteriorations. References: Balodis IM, Wynne-Edwards KE, Olmsted MC. The other side of the curve: examining the relationship between pre-stressor physiological responses and stress reactivity. Psychoneuroendocrinology 2010;35(9):1363–73 Shapiro S, Schwartz G, Bonner G. Effects of Mindfulness-Based Stress Reduction on Medical and Premedical Students. Journal of Behavioural Medicine 1998;21(6):581–99 Shapiro S, Shapiro D, Schwartz G. Stress Management in Medical Education: A Review of the Literature. Academic Medicine 2000;75(7):748–59